Household seed security: A case of maize and wheat seed systems in the mountains of Nepal - Atreya, Kishor; Gartaula, Hom Nath; Kattel, Kanchan (Elsevier, 2025)
"Context Household seed security enhances agricultural productivity and strengthens climate resilience, yet persistent seed insecurity remains a critical challenge in Nepal despite intervention efforts. Notably, women play a significant role in seed systems across developing countries, yet their contributions are frequently marginalised because of entrenched gender norms and socio-cultural barriers.